Prevalence of stress urinary incontinence and associated factors in elite female football players: better understanding for better prevention - Orhant, E.; Carling, C.; Maitre, C.; Muller, A.-S.; Van Niekerk, A.; Ferey, F.-X.; Chassard, T.; Dupuit, M.; Revault, A. (Journal of Science and Medicine in Sport, 2026)
Objectives Stress urinary incontinence (SUI) affects many female athletes. Beyond its psychological and social impact, SUI can also hinder performance. However, its effect in elite women's football has received little attention. This study aims to determine the prevalence of SUI in elite women's football, investigate its triggers, analyze compensatory strategies, and identify practical solutions to reduce its impact on health and performance. Design Observational, cross-sectional survey. Method This study used anonymized, retrospective data from 368 football players who completed an online questionnaire assessing the prevalence of SUI through both direct and indirect questions, triggering factors (TF) and the level of dialog on this topic. Sub-analyses were conducted to explore differences across practice levels (National: Division 1 and 2 (D1/D2), Division 3 and Under19 (D3/U19) and Regional: Other). Results Direct questions revealed that 19% of players reported suffering from SUI, while indirect indicators suggested a prevalence of 55%, with no significant difference between groups. Jumping/landing was the main trigger (41%), followed by running (27%), abdominal exercises (18%). 20% of players were asked about their SUI by physicians and 8% by coaches or physiotherapists, with no differences across practice levels. However, dialog with gynecologists (p<0.001) and physiotherapists (p=0.03) was significantly higher among top-level players D1/D2 compared to D3/U19 and Other. Conclusion SUI is common in women's football. This study emphasizes understanding the triggering factors for SUI prevention, treatment, and open discussion to avoid negative effects on athletes' health and performance. Coaches and healthcare professionals also play a key role in prevention.